2011
DOI: 10.1002/ibd.21517
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and long-term clinical outcomes for surgical patients with intestinal Behcetʼs disease

Abstract: According to the current study, volcano-shaped ulcers, higher CRP levels, a history of postoperative steroid therapy, and the presence of intestinal perforations detected by pathology were factors of a poor prognosis. Careful follow-up is required in surgical patients with these risk factors, who are at high risk for recurrence and reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 35 publications
1
61
1
1
Order By: Relevance
“…A retrospective analysis of 72 patients with intestinal Behçet's disease who underwent surgery in Korea showed that recurrence after surgical treatment was observed in 58.3% of patients, and reoperations were performed in 30.6% of patients. The cumulative recurrence rates after surgical treatment were 29.2% at 2 years and 47.2% at 5 years (20). Considering these reports, intestinal Behçet's disease, at least in some patients, should be recognized as a progressive disease resulting in severe bowel damage and requiring multiple surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of 72 patients with intestinal Behçet's disease who underwent surgery in Korea showed that recurrence after surgical treatment was observed in 58.3% of patients, and reoperations were performed in 30.6% of patients. The cumulative recurrence rates after surgical treatment were 29.2% at 2 years and 47.2% at 5 years (20). Considering these reports, intestinal Behçet's disease, at least in some patients, should be recognized as a progressive disease resulting in severe bowel damage and requiring multiple surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Although corticosteroids (CSs) and immunomodulators have shown efficacy in cases of intestinal BD, many patients become refractory to these drugs and some patients are intolerant to particular drugs, such as aminosalicylates, mesalazine, CSs, azathioprine (AZA) and colchicine, that are commonly used to treat BD. Surgery is an option when the condition becomes fulminant; however, BD can recur and a patient may require surgery on more than one occasion (3,4). Therefore, new approaches to treatment with long-term efficacy and good safety profiles are required for better therapeutic outcomes in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Among the clinical variables studied, previous surgery for perforation or fi stula was the only signifi cant factor associated with postoperative endoscopic recurrence. More recently, it is identifi ed volcano-shaped ulcers, higher CRP level (>4.4 mg/dL), and intestinal perforation on surgical pathology as independent predictors of recurrence [ 92 ]. Patients who received postoperative azathioprine had lower reoperation rates than those that did not.…”
Section: Postoperative Outcomesmentioning
confidence: 96%